(untitled) (Hekima Review, 2013)
In the traditional anthropology of Sub-Saharan Africa, individual and community are complementary and mutually generative. Moreover, this commu-nity extends in space and time, from the immediate blood relationship to all people (as seen in the value of hospitality), and to the not-yet-born and the deceased. Thus, the Western, Enlightenment-inspired worry that the group might stifle the individual who therefore needs ‘rights’ to be protected from the collectivity, is a notion imported with colonialism and reinforced by globalization. Yet modern Africans are not content with the Western style of ‘freedom from’, particularly in times of existential stress. Individual freedom, human rights and their interplay with morality, law and responsibilities need to be rethought for Africa in terms of its traditions and the ideal of ubuntu. Educators should make use of Africa’s vast storehouse of proverbs and dictums, myths and legends to inculturate African ways of speaking and living. The Church has a transformative as well as an inculturating role to play, particularly in appropriate teaching on marriage, children, and social and moral principles.